Nrf2/ARE Signaling Pathway: Key Mediator in Oxidative Stress and Potential Therapeutic Target in ALS - Susanne Petri; Sonja Körner; Mahmoud Kiaei (Neurology Research International)
Nrf2 (nuclear erythroid 2-related factor 2) is a basic region leucine-zipper transcription factor which binds to the antioxidant response element (ARE) and thereby regulates the expression of a large battery of genes involved in the cellular antioxidant and anti-inflammatory defence as well as mitochondrial protection. As oxidative stress, inflammation and mitochondrial dysfunctions have been identified as important pathomechanisms in amyotrophic lateral sclerosis (ALS), this signaling cascade has gained interest both with respect to ALS pathogenesis and therapy. Nrf2 and Keap1 expressions are reduced in motor neurons in postmortem ALS tissue. Nrf2-activating compounds have shown therapeutic efficacy in the ALS mouse model and other neurodegenerative disease models. Alterations in Nrf2 and Keap1 expression and dysregulation of the Nrf2/ARE signalling program could contribute to the chronic motor neuron degeneration in ALS and other neurodegenerative diseases. Therefore, Nrf2 emerges as a key neuroprotective molecule in neurodegenerative diseases. Our recent studies strongly support that the Nrf2/ARE signalling pathway is an important mediator of neuroprotection and therefore represents a promising target for development of novel therapies against ALS, Parkinson’s disease (PD), Huntington’s disease (HD), and Alzheimer’s disease (AD).